The Transition from Secondary Education to Higher Education: The Portuguese Situation - CHAGAS LOPES, Margarida (Journal of Research in Educational Sciences; Vol 9 No 1 (2018): JRES, Volume IX, Issue 1(11), 2018, 2019)
Decrease in the flow of students from Secondary to Higher Education in Portugal has been attributed by policy-makers to the attraction of the labour market for young people who should be continuing their studies. But several other reasons, which are generally missing in the official discourse, combine to create this decrease, including the role played by the State's social action policy for Higher Education, the shortness of families’ incomes, the level of schooling of the students’ parents, among others. Also psychological and sociological factors exist, which are often silenced, but which should also be considered to achieve a thorough understanding of the dynamics of flows from Secondary to Higher Education. These factors include the motivation, commitment and self-efficiency of students. This study starts with a macroeconomic and social approach, using comparative education methodology, to obtain a characterisation of the relative position of Portugal in the European Union (EU). This approach is described in this paper, where the main result is expected to be the conclusion that, among various factors, which include the inadequacy of public policies, the decisive factors for the decline in the flow of transition to Higher Education in Portugal are economic ones, namely access to income.